RELATIONSHIP BETWEEN FORMULA FEEDING AND DIARRHEA IN INFANTS AGED 0-6 MONTHS - Ahmad Ghiffari; Budi Utama; Liza Chairani; Fika Nurani Siti Aisyah (Bajang Institute, 2023)
Diarrhea is a state of defecation with the consistency of soft to liquid stools with a frequency of more than three times a day (more than four times a day in neonates) with or without bloody mucus. From birth to 6 months of age, Mother's Milk (ASI) is the best food with guaranteed nutritional value and cleanliness. However, parents often replace breast milk with other foods, such as formula milk, for specific reasons. Formula-fed babies are more prone to diarrhea. This study aims to determine the relationship between formula feeding and the incidence of diarrhea in infants aged 0-6 months. This type of research is an observational analytic with a cross-sectional design. The population and sample of this study were infants aged 0-6 months, and 70 samples were found that met the inclusion and exclusion criteria. The research sample was taken using the Consecutive Sampling Technique. The statistical test results showed a significant relationship between formula feeding and the incidence of diarrhea with a P-Value (of 0.000) and OR (19.125). This study concludes that there is a relationship between formula feeding and the incidence of diarrhea in infants aged 0-6 months.